Drone production, semen viability and spermatozoa longevity of Africanized Apis mellifera - André Luiz Halak; Pedro da Rosa Santos; Robson Marcelo Rossi; Priscila Wielewski; Gentil Vanini de Moraes; Vagner de Alencar Arnaut de Toledo (Acta Scientiarum. Animal Sciences, 2020)
Characteristics correlated with beekeeping production, less influenced by the environment and that can be controlled by management techniques, can help in the selection of colonies with higher production capacity, aiming to improve breeding programs. This research was carried out to evaluate the production of Africanized Apis mellifera drones and the longevity of spermatozoa from different genetic groups when supplemented with protein or not. Two genetic groups were used: one selected for royal jelly production from the Africanized honeybee breeding program and another without genetic selection. In both groups, the number of drone brood and the quality of semen were evaluated every 30 days, for five months. Statistical analysis was performed using Bayesian Inference. Statistical difference was found for the drone production among the treatments, and colonies without genetic selection produced more males (187.80 ± 11.15) than the selected colonies (93.07 ± 8.88). The selected colonies for royal jelly production presented greater efficiency in the reproductive cycle of males, because they produced fewer drones than colonies without genetic selection, however, with 31% greater semen viability.